INNOVATION STRATEGIES AS A NECESSARY CONDITION OF MODERN MANAGEMENT - NARZULLAEV N. S.; SOLIYEV I.I. (International Journal on Orange Technologies, 2020)
In this paper, Innovation Strategies are analyzed as a prerequisite for modern governance. The authors describe modern leading concepts of Innovation Management in the article. New methods of innovation management were discussed